Overlapping cusp ion dispersions formed by flux ropes on the day-side magnetopause - Burkholder, Brandon L.; Girma, Yohannes; Porter, Azzan; Chen, Li-Jen; Dorelli, John; Ma, Xuanye; Da Silva, Daniel; Connor, Hyunju; Petrinec, Steve (Frontiers in Astronomy and Space Sciences, 2024)
IntroductionCusp ion dispersion signatures reflect properties of remote magnetic reconnection. Since the cusp is easier to observe in situ compared to the reconnection x-line, ion dispersions provide key insight on whether reconnection is variable in space and time. This study is motivated by a specific dispersion signature having two ion populations separated in energy but not space. These are known as overlapping dispersions because when observed by low-Earth orbiting satellites traversing the cusp, they appear as two dispersed ion populations overlapping in magnetic latitudes. Overlapping dispersion signatures have been observed for all interplanetary magnetic field (IMF) orientations and have been associated with multiple reconnection processes, but the three-dimensional magnetic reconnection topology and particle trajectories have not been examined.MethodsForward particle tracing using the GAMERA-CHIMP global magnetohydrodynamic (MHD) with test particle framework is carried out to construct ion dispersion signatures throughout the cusp. Under idealized solar wind driving with steady purely southward IMF, both standard and overlapping dispersions are found.ResultsAnalysis of the test particle trajectories shows that the higher energy population of the overlapping dispersion travels along the axis of a flux rope before heading into the cusp, whereas the lower energy population goes directly into the cusp. Furthermore, the overlapping dispersions observed by the synthetic satellites compare well to Defense Meteorological Satellite Program (DMSP) F16 observations during strongly southward IMF.DiscussionIt is thus concluded that during strongly southward IMF, cusp-entering particles interacting with a magnetopause flux rope (generated by secondary reconnection) is one way to produce an overlapping dispersion. This study lays the groundwork for the forthcoming NASA Tandem Reconnection and Cusp Electrodynamics Reconnaissance Satellites (TRACERS) mission, which will connect the cusp to the magnetosphere—discovering how spatial or temporal variations in magnetic reconnection drive cusp dynamics. The expected launch of TRACERS is in 2025.